Pengaruh Perceived Ease Of Use, Perceived Security Dan Trust Terhadap Decision To Adopt Digital Payment: Studi Kasus Pengguna Marketplace Meta Di Dki Jakarta - By Luthfi Hamdi; Umi Widyastuti; Shandy Aditya (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to examine the factors that influence Perceived Ease of Use, Perceived Security, Trust and the Decision to adopt Digital Payment. There four variables used in this study are, Perceived Ease of Use, Perceived Security, Trust and Decision to Adopt Digital Payment. This he study was conducted in the Jakarta Special Capital Region (DKI Jakarta). A quantitative research method was employed using a Likert scale for measurement, with the population being Marketplace Meta (Facebook) users aged 17-30 in DKI Jakarta. In this study, purposive sampling was utilized to obtain 260 respondents. The research analysis technique employed Structural Equation Model (SEM). The results indicate that Perceived Ease of Use and Perceived Security have a significant direct effect on Trust, and Perceived Ease of Use, Perceived Security and Trust have a significant direct effect on the Decision to Adopt Digital Payment and Perceived Ease of Use and Perceived Security have a direct effect on the Decision to Adopt Digital Payment via Trust mediation.